2018
DOI: 10.1016/j.jmii.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoenolpyruvate phosphotransferase system components positively regulate Klebsiella biofilm formation

Abstract: The genes, KPN00353-KPN00352-KPN00351, encode a putative enzyme II complex in PTS and positively regulate biofilm formation by enhancing production of eDNA and capsular polysaccharide in K. pneumoniae. Five proteins related to chaperones, to the citric acid cycle, and to quorum sensing are upregulated by the KPN00353-KPN00352-KPN00351 system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…We observed reduced 1,3-PD production in this study ( Figure 3A ) and increased capsular polysaccharide production in the previous study ( Horng et al, 2017 ) in K. pneumoniae overexpressing KPN00353-KPN00352 - KPN00351 incubated under microaerobic conditions compared with that of the vector control. This finding is consistent with the study by Guo et al (2010) reporting that non-capsulated K. pneumoniae provided a higher 1,3-PD yield.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…We observed reduced 1,3-PD production in this study ( Figure 3A ) and increased capsular polysaccharide production in the previous study ( Horng et al, 2017 ) in K. pneumoniae overexpressing KPN00353-KPN00352 - KPN00351 incubated under microaerobic conditions compared with that of the vector control. This finding is consistent with the study by Guo et al (2010) reporting that non-capsulated K. pneumoniae provided a higher 1,3-PD yield.…”
Section: Resultssupporting
confidence: 71%
“…KPN00353 encodes 147-amino-acid (aa) putative EIIA homologue. KPN00352 and KPN00351 encode putative EIIB (95 aa) and EIIC (445 aa) homologues respectively ( Horng et al, 2017 ). Therefore, the purpose of this study was to examine the effects of KPN00353-KPN00352 - KPN00351 on the 1,3-PD production.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous data showed that overexpression of KPN00353-KPN00352-KPN00351 increased biofilm formation by K. pneumoniae MGH78578 (Horng et al, 2018). In STU1, we found homologs having high sequence identity to KPN00353 (98%), KPN00352 (100%), and KPN00351 (99%) of MGH78578, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, these three assays in the report by Luo et al (2017) did not allow direct observation of type 3 fimbriae synthesis such as Western blotting using antibody specific to type 3 fimbriae. Some other factors in K. pneumoniae may affect the results of MRHA (Stahlhut et al, 2012), mannan-binding assay (Madison et al, 1994), and bacterial adhesion assay (Chung, 2016; Horng et al, 2018). Therefore, the regulation of MRHA, mannan-binding assay and bacterial adhesion assay by KP1-4563 depending on type 3 fimbriae or not is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation